Eficiência do uso da terra na associação de culturas para produção de Bio-Óleo - Basílio, Flávio de Oliveira (Universidade Federal Rural do Semi-Árido, 2010)
A field experiment was carried out at Morrinhos, municipality of Nísia Floresta, RN with the goal of developing a management system aiming to produce oil for biodiesel. In this system, hybrid coconut (Cocos nucifera L.) is the main crop, and is associated with sunflower, castor bean, peanut, soybean and jatropha cultivation in fertilized. The experimental design was randomized blocks with six treatments in a consortium (coconut and sunflower hybrids - C1, hybrid coconut and castor oil - C2, hybrid coconut and peanuts - C3, hybrid coconut and soy - C4, hybrid coconut and jatropha - C5 and jatropha and sunflower - C6) and six in monocrop (S1 hybrid coconut, sunflower - S2, castor - S3, peanuts - S4, soy - and jatropha S5 - S6) with three replications. Plots of 768 sqm with 12 coconut palm trees spaced 8.0 x 8.0 m square in the intercropping systems. Sole crops and intercropped with jatropha and sunflower were planted in an area of 240 m² per plot and the trial had a floor area of 1.602 ha. The variables were analyzed: grain yield and oil content by the production system, also estimating the efficiency of land use (EUT), corresponding to the 1st year of conducting the experiment and the 12 th year of cultivation of coconut, quantifying the production of bio-oil systems studied. There was no significant difference in total production of bio-oil treatments between the consortium that promotes the association of oil without causing damage to coconut palms. There were significant differences in total production of bio-oil systems in monoculture. The highest yields were given by peanut, rapeseed and sunflower did not differ. The minors were of jatropha in the first year. The intercropping system with higher efficiency of land use were: coconut x sunflower and coconut x soybeans emerging as the greatest potential to increase the production of bio-oil.
Efficiency of land use in the crop association to produce Bio-Oil
Keywords: Consórcio de oleaginosas; Bio-óleo; Uso da terra; Consortium of oil; Bio-oil; Land use; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO